Hak Pendidikan Karakter bagi Anak Perspektif Al-Qur’a>n (Kajian Tafsir Al-Miṣbāḥ) - Zahroh, Umi (MAN 1 Kota Kediri, 2022)
This research departs from the problem of character education in Indonesia which has not been successfully demonstrated by the condition of the nation's generation of characters that is getting worse, such as the occurrence of juvenile delinquency. This study aims to reveal the Human Rights Paradigm of character education for children as well as the concept of character education for children from the perspective of the Qur'an. This study uses a qualitative research approach with the mawḍū'ī (thematic) study method using al-Miṣbāḥ interpretation. The results of this study indicate that the State of Indonesia and the Qur'an strongly protect children's human rights to obtain an education.